Effects of keratinocyte growth factor on skin epithelial differentiation of human amnion epithelial cells - Fatimah S.S.; Tan G.C.; Chua K.; Tan A.E.; Nur Azurah A.G.; Hayati A.R. (2024)
Indexed by WOS/SCOPUS